Stress Measurements for Safety Decisions in Longwall Coal (4b24fd83-539f-4e52-8928-06b50544afce) - Eric Zahl (International Conference on Ground Control in Mining, 2002)
Researchers at the Spokane Research Laboratory of the National Institute for Occupational Safety and Health, Spokane, WA, have collaborated with three Western longwall coal mines in an ongoing effort to develop technologies that will aid in providing safe and stable working areas. The goal of the research described here is to develop a stress monitoring system that will provide immediate information to mine managers for making daily safety decisions as areas of poor ground are mined through. Initial work has focused on answering preliminary questions regarding the reliability and use of stress change patterns. Research is concentrated on monitoring horizontal stress because horizontal stress is transmitted over long distances through stiff strata, thus allowing an extended length of entry to be monitored. This paper presents an explanation of the concept, key results from field tests at two mine sites, and a proposed process for imple¬menting a monitoring system. System design layouts, instrument use, data collection and interpretation methods, and processes to present findings to mine staff are described. Additional validation and correlation with actual failure mechanisms are required before this approach can be recommended at ongoing operations. How¬ever, initial results indicate that this approach shows promise in mines prone to bumps and roof falls associated with large stress changes. In particular, analyses of measured changes in horizontal stresses appear useful.